2010
DOI: 10.1016/j.jsr.2009.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating construction safety risks using prevention through design

Abstract: Introduction: Research and practice have demonstrated that decisions made prior to work at construction\ud sites can influence construction worker safety. However, it has also been argued that most architects and\ud design engineers possess neither the knowledge of construction safety nor the knowledge of construction\ud processes necessary to effectively perform Construction Hazards Prevention through Design (CHPtD).\ud Method: This paper introduces a quantitative methodology that supports designers by provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 22 publications
1
78
0
8
Order By: Relevance
“…DfS, which is also referred to as Designing for Construction Safety (DfCS) (Behm, 2005a), Prevention through Design (PtD) (Schulte, et al, 2008;Ku, 2014), safe design (Safe Work Australia, 2012) and Construction Hazards Prevention through Design (CHPtD) (Toole and Gambatese, 2008;Gangolells, et al (2010), is the deliberate consideration of construction site safety in the design phase of a project (Behm, 2005a). The main notion is that, by addressing safety during the design process, hazards will be eliminated or reduced during construction (Behm, 2005a).…”
Section: Design For Safety With Consass Assessmentmentioning
confidence: 99%
“…DfS, which is also referred to as Designing for Construction Safety (DfCS) (Behm, 2005a), Prevention through Design (PtD) (Schulte, et al, 2008;Ku, 2014), safe design (Safe Work Australia, 2012) and Construction Hazards Prevention through Design (CHPtD) (Toole and Gambatese, 2008;Gangolells, et al (2010), is the deliberate consideration of construction site safety in the design phase of a project (Behm, 2005a). The main notion is that, by addressing safety during the design process, hazards will be eliminated or reduced during construction (Behm, 2005a).…”
Section: Design For Safety With Consass Assessmentmentioning
confidence: 99%
“…If human error in the construction industry can be effectively reduced, the occurrences of construction accidents can be minimized [3,4]. Previous studies revealed that if the factors of facilities, work methods and operations, processes, equipment, tools, products, new technologies, and work organization that lead to human error in the work environment can be eliminated by an effective workplace environment, the probability of human error can be greatly reduced, and the occurrence of accidents can be controlled [5,6]. "Workplace environment" ordinarily refers to the environment of workplace in a location during the construction itself, that is, structural and product workplace environments.…”
Section: Importance Of Workplace Environment In Effectivementioning
confidence: 99%
“…A matter of special interest lies in the consideration of prevention right from the project stage (Lorent, 1987;Haslam et al, 2005;Behm, 2005;Gangolells, Casals, Forcada, Roca & Fuertes, 2010). Previous studies highlight the relationship between design and safety, and that the consideration of safety already from the design phase is an effective technique to reduce or eliminate risk situations.…”
Section: Risk Assessmentmentioning
confidence: 99%